Alterações fisiológicas e metabólicas em Hyptis fruticosa Salzm. ex. Beth e Ocimum gratissimum L. sob diferentes regimes hídricos - Coêlho, Maria Reis Valois (2014)
Hyptis fruticosa Salzm. Ex. Benth and Ocimum gratissimum Lindi are species from lamiaceae family of great medicinal importance, notwithstanding, they have been goals of few studies related to the cultivation techniques. Therefore, the study’s goal was to evaluate the behavior and tolerance of plants of H. fruticosa and O. gratissimum cultivated in vases submitted to different levels of evapotranspired water reposition during thirteen days (H. fruticosa) and nine days (O. gratissimum). The experiment was made in greenhouse under randomized complete block design with four treatments (100, 75, 50 and 0% of evapotranspired water reposition). It was verified that there were not any significant difference of total dry mass and leaf area among the treatments in the species H. fruticosa and O. gratissimum. Both of them presented the lowest values of relative water content, water potential, chlorophylls and carotenoids in the water reposition 0% treatment. In O. gratissimum, there was the decrease in net assimilation of carbon, stomatal conductance and transpiration with the water deficit increase, but the CO2 inside concentration was higher in the water reposition 0% treatment. The two species presented amino acid accumulation, proline, soluble proteins and soluble carbohydrate according to the water deficit increase. The essential oil content increased with the water availability increment in O. gratissimum, but it did not present the significant difference among the treatments in H. fruticosa. O. gratissimum revealed itself more sensitive and H. fruticosa more tolerant to the water deficiency.